ANALYSES OF PORE PRESSURE AND INSITU STRESS IN TUNU FIELD, KUTAI BASIN - FADLAN (NIM: 22015309), DHANNY
The Tunu Field is the largest gas field in the Mahakam Delta discovered in 1980, and it has been producing gas since 1990 until now. The production in this field causes some side effects, and one of the effects is reservoir depletion. This circumstance is thought to be the cause of a drilling problem, i.e. lost circulation. The analyses of pore pressure (Pp) and insitu-stresses are performed in order to know the relationship between them in the study area. The distribution of pore pressure is analysed by performing the mapping of lateral and vertical distributions of overpressure and depleted pressure zones. Meanwhile, the analysis of insitu stresses is performed by calculating the magnitude of Shmin, Sv, and SHmaks, and determining their directions. The analyses of Pp and Shmin show that there is coupling relation between them in the Tunu Field. This relationship is proven by the increase in hydraulic fracture value starting at the top of overpressure, and by the presence of the lost circulation zone that is coinciding with the presence of depleted reservoir zone. The lost circulation is caused by the decrease in pore pressure affecting the decrease in Shmin, so that the rock is unable to hold pressure from drilling mud and initiating fracture in rock. The coupling ratio of ΔShmin/ΔPp in overpressure zone shows a relatively low value. This condition indicates that the overpressure is more the cause rather than the effect of the increase in Shmin in that zone.